Approaching coupled cluster accuracy with a general-purpose neural network potential through transfer learning - Justin S. Smith (Nature Portfolio, 2019)
Computational modelling of chemical systems requires a balance between accuracy and computational cost. Here the authors use transfer learning to develop a general purpose neural network potential that approaches quantum-chemical accuracy for reaction thermochemistry, isomerization, and drug-like molecular torsions.